1095 The Utility of Plasma Circulating Cell-Free Messenger RNA as A Biomarker of Glioma: A Pilot Study. (12th October 2021) - Ita, M; Wang, J H; Toulouse, A; Lim, C; Fanning, N; O'Sullivan, M; Nolan, Y; Kaar, G; Redmond, H
Abstract: Introduction: Research into the potential utility of plasma-derived circulating-cell-free nucleic acids as non-invasive adjuncts to radiological imaging has been occasioned by the invasive nature of brain tumour biopsy. Circulating-cell-free messenger RNAs are short fragments of RNA present in blood. The objective of this study was to determine whether significant differences exist in the plasma transcriptomic profile of glioma patients relative to differences in their tumour characteristics, and also whether any observed differences were representative of synchronously obtained glioma samples and TCGA glioma derived RNA. Method: Blood samples were collected from twenty-nine patients prior to tumour resection. Plasma-ccfmRNA and glioma derived RNA were extracted and profiled. Results: BCL2L1, CXCL5, GZMB, HLA-A, HLA-C, IRF1, MYD88, TGFB1, TLR2, and TP53 genes were significantly over-expressed in glioma (high-grade-glioma-HGG and low-grade-glioma-LGG) patients (p < 0.05, versus control). BCL2L1, GZMB and HLA-A genes were significantly over-expressed in HGG patients (p < 0.05, versus LGG patients). There was positive correlation between the magnitude of fold change of differentially expressed genes in plasma and glioma derived RNA (Spearman r = 0.6344, n = 14, p = 0.017), and with the mean FPKM of TCGA glioma derived RNA samples (Spearman r = 0.4614, n = 19, p = 0.047). There was positive correlation between glioma radiographic tumour burden and the magnitude of fold change of CSF3 gene (r = 0.9813, n = 20, p < 0.001). Conclusions: We identified significant differential expression of genes involved in cancer inflammation and immunity among patients with different glioma grades, and we identified positive correlation between the plasma transcriptomic profile and tumour samples, and with TCGA glioma derived RNA.